Effect of Sal (Shorea robusta) seed meal on growth and carcass quality in broiler - Rahman, M; Ahammed, M; Hossain, ME; Howlider, MAR; Kabir, AKMA (Bangladesh Journal of Animal Science, 2017)
This study was conducted to investigate the effect of dietary sal (Shorea robusta) seed meal (SSM) on growth performance, carcass characteristics and economic feasibility in broilers. Two hundred day-old, straight-run (Cobb-500) broiler chicks were randomly allocated to five dietary treatments for 42 days feeding trial (40 birds each). Dietary treatments were designed according to SSM supplementation levels, namely control diet (0% SSM), diets containing 10 and 15% of un-boiled SSM (USSM), and diets containing 15 and 20% of boiled SSM (BSSM). At the end of feeding trial, 20 birds (2birds per replication) were subjected for determining the meat yield parameters. Overall weight gain of control and 0% BSSM 2group was higher (p<0.001) than that of other groups. Feed consumption was higher in control and 20% BSSM group where as 15% USSM group exerted the lowest. Poorest FCR and performance index were showed in the birds of 15% USSM supplemented group. There were no differences in meat yield parameters among treatments. Total profit per kg live broiler was significantly (p<0.001) higher on diet with 20% BSSM. The boiling of SSM was effective to reduce the tannin-related depression on the performance of broilers. In conclusion, broilers received diets containing BSSM up to 20% showed better growth performance along with profitability, and this boiled SSM could be used as an alternative energy source ingredient in broilers having no detrimental effects on performance. Bang. J. Anim. Sci. 2017. 46 (1): 10-16